Understanding The Causes Of Child Labor And Its Sectoral Distribution In Turkey - Kanun, Orçun (Institute of Social Sciences, 2018)
Both in world and in Turkey, child labor still continues to be a major problem. The nature of describing the causes of this issue is complex. However, this dissertation focuses on the causes of child labor and its sectoral distribution in Turkey. In this focus, this thesis explains that the causes of child labor using probit and weighted probit models with several factors such as characteristics of households, children related factors, demographic decomposition of household and spatial factors. Moreover, multinomial logit model is used to which sectors are considerably affected by these factors.

Hem dünyada hem de Türkiye'de çocuk istihdamı hala büyük bir problem olmaya devam ediyor. Doğası gereği çocuk işçiliğinin sebeplerini açıklamak karmaşık. Ancak, bu tezin odaklandığı nokta çocuk işçiliğinin nedenlerini ve Türkiye'deki çocuk işçilerin sektörel dağılımını anlamlandırmaktır. Bu odak çerçevesinde, bu tez, hane halkının özelliklerini, çocuk ile ilişkili faktörleri, hane halkı ve mekansal faktörlerin demografik ayrışmasının, çocuk işçiliği üzerindeki etkisinin derecesini, probit ve ağırlıklı probit modellerini kullanarak açıklar. Ek olarak, hangi sektörlerin saydığımız bu faktörlerden önemli ölçüde etkilendiğini karşılaştırmalı olarak çok sınıflı lojit yöntemiyle analiz eder.
Türkiye'deki Çocuk İşçiliğinin Sebeplerini Ve Sektörel Dağılımını Anlamak
Thesis (M.A) -- İstanbul Technical University, Institute of Social Sciences, 2018
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Econometrics; Economics; Working children; Child labor; Ekonometri; Ekonomi; Çalışan çocuklar; Çocuk işgücü